Implementasi Program Pengembangan Desa Pesisir Tangguh (PDPT) di Desa Wonorejo Kecamatan Kaliwungu Kabupaten Kendal - Widayatma, Vicky Cahyalita; Harsasto, Priyatno (Journal of Politic and Government Studies, 2017)
Abstract Wonorejo village, Kaliwungu sub-district is one of the three coast villages in Kendal regency which becomes the implementation place for Resilient Coastal Rural Development program (Pengembangan Desa Pesisir Tangguh) as known as PDPT in 2012 until 2014. Basicly, PDPT contents stresses more in institutional strengthen activity, the building of infrastructure and environment, human resources and the independence of people around coastal area especially, for this research, is the strength of Wonorejo village, Kaliwungu sub-district, Kendal regency.Research method that is used in this research is qualitative approach with data collecting techniques are observation, interview, and document study. Informants of this research are Fishery and Naval Department (Dinas Kelautan dan Perikanan), Functionary of Wonorejo village, Kaliwungu sub-district, Kendal regency, PDPT team of Wonorejo village, and Coastal People Group (Kelompok Masyarakat Pesisir) a.k.a KMP.This research result shows that in the implementation, all the elements that take role in PDPT program have done their tasks and functions well, so the people around receive various benefits especially in the building of infrastructure. Now, the mobility of people in Wonorejo village is easier and it makes a good development of their life quality to be better than before.Recommendation that can be given in this research is that KMP is not related with financial area has to keeping an eye on the result of their work, so they can minimalize drastic decreasing of value. Moreover, if problems happen, it can be reported directly into relatable Department. Fishery and Naval Department of Kendal regency has to work along with Industrial Department, Koperasiand, and UMKM (Dinas Perindustrian, Koperasi, dan UMKM) in solving various problems faced by KMP that have correlation with Food Production. Key Words: Implementation; Resilient Coastal Rural Development; Building; Empowerment